2016
DOI: 10.1016/j.biortech.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the value of bioproducts from different stages of anaerobic membrane bioreactors

Abstract: The anaerobic digestion process in anaerobic membrane bioreactors is an effective way for waste management, energy sustainability and pollution control in the environment. This digestion process basically involves the production of volatile fatty acids and biohydrogen as intermediate products and methane as a final product. This paper compares the value of bioproducts from different stages of anaerobic membrane bioreactors through a thorough assessment. The value was assessed in terms of technical feasibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Other possible route for the system is biohydrogen production which contains no environmental harm as an energy source (produce only H 2 O as a combustion product) and has very little environmental impact when compares with other AnMBR products e.g. volatiles fatty acid (VFA) and methane (Khan et al, 2016). In this regard, biohydrogen production from AnMBR could be one vital alternative to make the emerging technology as pilot/commercial success with no harm to the environment.…”
Section: Environmental and Economic Assessment Of Biohydrogen Productmentioning
confidence: 99%
See 2 more Smart Citations
“…Other possible route for the system is biohydrogen production which contains no environmental harm as an energy source (produce only H 2 O as a combustion product) and has very little environmental impact when compares with other AnMBR products e.g. volatiles fatty acid (VFA) and methane (Khan et al, 2016). In this regard, biohydrogen production from AnMBR could be one vital alternative to make the emerging technology as pilot/commercial success with no harm to the environment.…”
Section: Environmental and Economic Assessment Of Biohydrogen Productmentioning
confidence: 99%
“…Fermentative bacteria can produce hydrogen gas continuously without any light source in anaerobic wastewater treatment (Kumar et al, 2017;Tao et al, 2007). In addition to hydrogen, such bacteria can produce other products to satisfy their metabolic needs and to further growth, these include organic acids, alcohol and acetone that can be converted into electricity sources, biodegradable plastics and fibers (Hallenbeck, 2005;Khan et al, 2016). Therefore, dark fermentation seems more feasible and there is remarkable progress ongoing toward practicality (Das & Veziroglu, 2008;Hawkes et al, 2007;Kraemer & Bagley, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VFAs, otherwise referred to as short chain fatty acids (SCFAs) that include acetate, butyrate, and propionate, are intermediate and/or end products of the digestion process, and their concentrations have been observed to correlate with overall functionality of the anaerobic treatment process (Ahring et al 1995; Hino et al 1993; Lin 1993; Varel et al 1977) In recent years, VFAs have been identified as useful sources for the subsequent production of valuable bio-products (e.g., biopolymers, biofuels, and reduced chemicals of high values, such as alcohols, aldehydes, ketones, and esters) (Bhatia et al 2015; Khan et al 2016; Setiadi et al 2015). Given the potential value of produced VFAs and their direct relationship with the functionality of the anaerobic digestion process, a further understanding of their accumulation in wastewater treatment systems is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic conversion of organic matter to methane has been widely recognized as an efficient technology for simultaneous waste treatment and energy generation (Batstone and Virdis 2014;Choi et al 2013;Holm-Nielsen et al 2009;Khan et al 2016;Liu et al 2011;Mackie and Bryant 1995;Nasir et al 2012;Tada et al 2006;Vandevoorde and Verstraete 1987). Anaerobic digestion usually undergoes several steps: disintegration, hydrolysis, fermentation and methanogenesis (Chan et al 2009).…”
Section: Introductionmentioning
confidence: 99%